2021
DOI: 10.2147/ijgm.s302735
|View full text |Cite
|
Sign up to set email alerts
|

A Scale for Predicting the Outcomes of Patients with Epilepsy: A Study of 141 Cases

Abstract: Objective This study aimed to identify the factors relevant for developing a scale to estimate the prognosis of patients with epilepsy. Methods This study followed 141 patients with newly or previously diagnosed epilepsy for between four and nine years. The patients were divided into three groups on the basis of their outcomes during the follow-up period: patients that were seizure-free without anti-epileptic drugs (AEDs) (group A, n = 48), patients with pharmacorespons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Several studies have investigated risk factors for epilepsy in infants, such as that by Heggstad and Hafstrom [12]. According to In other studies [15,16], some authors have reported a scoring system of epilepsy to predict the neurological outcomes or prognosis of epilepsy, but there is no scoring system for epilepsy diagnosis. In this study, eight patients were diagnosed with infantile spasms, which could be a possible confounding factor of the scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated risk factors for epilepsy in infants, such as that by Heggstad and Hafstrom [12]. According to In other studies [15,16], some authors have reported a scoring system of epilepsy to predict the neurological outcomes or prognosis of epilepsy, but there is no scoring system for epilepsy diagnosis. In this study, eight patients were diagnosed with infantile spasms, which could be a possible confounding factor of the scoring system.…”
Section: Discussionmentioning
confidence: 99%